Step 1: Analyze the limit as \( x \) approaches \(-\infty\)
We are tasked with evaluating the limit:
\[
\lim _{x \rightarrow-\infty} \frac{1 - x^{2}}{1 + x^{2}}
\]
Step 2: Divide numerator and denominator by \( x^{2} \)
To simplify the expression, divide both the numerator and the denominator by \( x^{2} \), the highest power of \( x \) in the denominator:
\[
\lim _{x \rightarrow-\infty} \frac{\frac{1}{x^{2}} - 1}{\frac{1}{x^{2}} + 1}
\]
Step 3: Evaluate the limit of each term
As \( x \rightarrow -\infty \), \( \frac{1}{x^{2}} \rightarrow 0 \). Substitute this into the expression:
\[
\frac{0 - 1}{0 + 1} = \frac{-1}{1} = -1
\]